Replenish Millions of Kenyan Household’s Granaries Through Forest Restoration - Mutune, Jane (University of Nairobi, 2020)
Forest degradation has also triggered the scarcity of resources and resulted in conflicts between government and Community Forest Associations (CFAs). Recent conflicts have been witnessed at the Maasai Mau, Cheregani and Mt. Elgon forests. Further, forest destruction precariously exposes women and girls as they walk long distances to fetch fuelwood. About 82 per cent of households use fuelwood for cooking and 1.2 per cent for lighting (KIHBSP, 2017). However, Kenya is only able to meet about 70 per cent of this demand through sustainable domestic supply. The annual deficit of 12 million cubic meters is met by formal and informal imports plus unsustainable extraction from natural forests (KIHBSP, 2017). The situation can be reversed through forest restoration and meaningful involvement of the CFAs in forest co-management.
Keywords: Forestry; Kenya